Acute diarrheal diseases in the pediatric population in Ecuador 2013-2023: systematic review - Astudillo, Luis Á.; Alcívar, Lisa M.; Briones, Juriana N.; Chica, Karen A.; Reyes, Ana C.; Sánchez, Génesis N. (Revista Gregoriana de Ciencias de la Salud, 2024)
Acute diarrheal diseases (ADD) represent one of the significant challenges for health systems worldwide, especially affecting children and communities with limited resources. This review aimed to analyze the main etiological agents and associated factors that have influenced the prevalence of acute diarrheal diseases in Ecuadorian children. Through an exhaustive review of secondary literature in databases and electronic journals, 32 studies were reviewed that highlight viruses as the main causal agents of ADD in children in Ecuador, with rotavirus being the most predominant. Although much research in the country focuses on the study of bacteria as causes of ADD, viruses are globally recognized as the main responsible for these diseases.